The mind & muscles: Introducing a validated EEG/EMG protocol for recording cognitive-muscular interactions in experimental archaeology - Brienna Eteson; Simona Affinito; Fotios Alexandros Karakostis (PLoS ONE, 2025)
Despite extensive research into the biomechanical and cognitive dimensions of early hominin material culture, no study has explored these aspects together in the context of stone tool production and use. In contrast to fields like rehabilitation and sports science, where electroencephalography (EEG) and surface electromyography (sEMG) are often integrated, experimental archaeology lacks such a combined approach. This paper introduces and validates a new protocol that integrates EEG and sEMG to measure neuromechanical activity during a classic stone tool task: cutting leather with a flake. Our experimental design divides the task into three phases: Hold, Aim, and Execute. Consistent with our expectations, results show that all eight muscles are most active during task execution, with the non-dominant hand playing a key role in stabilization during both the Aim and Execute phases. In the preparatory Aim stage, we observed increased beta power in the left frontal region (linked to planning, problem-solving, and working memory) as well as heightened motor activity associated with using the non-dominant hand, which contributes to the stabilization of the target material during this stage. During the Execute phase, beta power in these cortical areas decreased, with peak muscle activation occurring alongside suspected beta desynchronization in the motor region, reflecting intensified movement activity. Overall, these findings closely align with our expectations, validating our combined EEG-sEMG protocol and highlighting the importance of segmenting tool-using tasks into distinct phases, which allows for the identification of dynamic brain-hand interactions throughout the process. The proposed step-by-step protocol offers a new methodological basis for future research into the complexities of hominin behaviors and tool use.